Efektivitas Terapi dan Kejadian Tidak Dikehendaki Penggunaan Regimen Pengobatan Jangka Pendek pada MultiDrug-Resistant Tuberculosis: a Scoping Review - Yunilistianingsih - Yunilistianingsih; Vitarani Dwi Ananda Ningrum (Jurnal Farmasi Indonesia, 2023)
The increase in Multidrug-resistant Tuberculosis (MDR-TB) is a global problem that must be addressed immediately. Duration of treatment, adverse events (ADRs) and medical costs can affect adherence and treatment success. This literature review was conducted to review the effectiveness and ADRs of short-term regimens (STR) in MDR-TB patients. We used PubMed, ScienceDirect, and Google Scholar to retrieve the relevant original articles on MDR-TB treatment with STR in English-language, published from 2018 through 2022. The keywords used in the search for articles are "multi-drug-resistant tuberculosis", "short regimens" or "short-term regimens", effectiveness, safety" or "adverse events". Of the 13 articles obtained, the all-oral regimen proved promising for implementation in the treatment of MDR-TB. Based on sputum conversion, cure rate, and percentage of patients who completed treatment, the regimen with the highest therapeutic effectiveness was 6KmMfxPtoCfzHEZ/5MfxCfzEZ at 92.9%, and the lowest was 4KmMfxPtoCfzHEZ/5MfxCfzEZ at 63.6%. The all-oral regimen with or without Bedaquilin showed a better average therapeutic effectiveness (87.04%) than regimen containing injection (78.43%). Meanwhile, the serious ADRs that emerged were death, cardiotoxicity, hepatotoxicity and ototoxicity. Apart from monitoring the safety, research needs to be expanded to a larger population and wider sites, to find more effective regimens because Mycobacterium tuberculosis are easily resistant.